Inhibitory activity of cyclohexenyl chalcone derivatives and flavonoids of fingerroot, Boesenbergia rotunda (L.), towards dengue-2 virus NS3 protease. - Tan, Siew Kiat *; Pippen, Richard; Rohana Yusof; Halijah Ibrahim; Norzulaani Khalid; Noorsaadah Abd Rahman (Elsevier Ltd, 2006)
Boesenbergia rotunda (L.) cyclohexenyl chalcone derivatives, 4-hydroxypanduratin A and panduratin A, showed good competitive inhibitory activities towards dengue 2 virus NS3 protease with the Ki values of 21 and 25 microM, respectively, whilst those of pinostrobin and cardamonin were observed to be non-competitive. NMR and GCMS spectroscopic data formed the basis of assignment of structures of the six compounds isolated.